Developing an Instrument for Measuring the Implementation of Inclusive Education in Universities - Iswari, Mega; Budi, Setia; Arnes, Gaby; Triswandari, Retno; Taufan, Johandri; Zulmiyetri, Zulmiyetri; Nurhastuti, Nurhastuti; Safaruddin, Safaruddin; Utami, Iga Setia; Kusumastuti, Grahita (Department of Special Education, 2024)
This research aims to develop an instrument to measure the implementation of inclusive education in universities. The research was developed using a mixed-methods approach, which combines the Theoretical Framework and Needs Assessment. The first stage of the research involved literature review to investigate the relevant instrument and references that support the development of an instrument for measuring inclusive education in universities. The second stage was a needs assessment conducted at universities in Padang. The subjects of the research were 47 university students from four universities in Padang. The data were analyzed using focus group discussion. The study of the index for inclusion for higher education was compared to the results of the research. Findings of the research showed that five aspects are needed to develop the instrument of index for inclusion in universities. Lecturers and students also selected the five aspects to be the obligatory aspects that should be placed in the instrument of the implementation of inclusive education. The instrument developed in this research is the instrument of index for inclusion, which is divided into five aspects. The five aspects were developed based on a literature review. The results of the research are expected to be the guide in measuring the implementation of inclusive education in universities and help students with special needs to be provided with physical and non-physical accessibilities in universities.